PENGARUH KECEMASAN TENTANG PANDEMI COVID-19 TERHADAP PENGELUARAN ASI IBU POST PARTUM - Inge Anggi Anggarini; Rezah Andriani (Jurnal Delima Harapan, 2022)
Post partum is the period or time since the baby is born and the placenta comes out of the uterus, until the next six weeks, accompanied by the recovery of organs related to the womb, which undergo changes such as injuries and others related to childbirth. The post partum period is a time when the mother experiences a change in her role. The aims: the effect of the anxiety of the covid-19 pandemic on the production of breast milk for postpartum mothers. The Method: This study uses a cross sectional approach and non-probability sampling is used for sampling. Results: there is an effect of the anxiety of the covid-19 pandemic on the expenditure of breast milk for postpartum mothers (p <0.05). Conclusion: That anxiety facing the covid-19 pandemic can affect breast milk production so that more education and motivation are needed from health workers, husbands and families.